(3eTJHg GdfSHIs - (3YHO GdZfj Hf SYjO, ef GdCRO, CHh eMeO GdGROj,J (B409 (3g` s ((3GSeGYjd Hf eMeO Hf CMeO Hf eMeO Hf Sgjd GdebQi GdeYQha GdfbGT s)
(3ChdgG (B:s
(3GeG HYO aEfi deG VaJ cJGHi ai eDJda CSeGA GdeMOKjf heNJdagG s
(3GfXQ Qbe (B476 (3JGQjNs
(3QhGjg CHj RcQjG YHOGdQMef Hf CMeO GdHNGQis
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs